Revisit to the Estimation of Percolation Thresholds in Electrical Conducting Nanocomposites - Lu, Chunsheng (Engineers Australia, 2010)
The critical volume fraction or percolation threshold of nano-fillers is a key parameter in optimising electrical conducting nanocomposites. In this paper, several models based on the concepts of mean field, excluded volume and renormalisation are introduced and applied to study the influence of geometrical factors of nano-fillers such as aspect ratio and dimension on percolation thresholds. The relationships obtained from these models can be used to estimate the percolation thresholds of nanotubes and graphene in nanocomposites. Some efficient methods for controlling the percolation threshold of a given nano-filler in polymer matrix are discussed.